Marsch nach Bern 1969: Emilie Lieberherr hält eine Rede auf dem Bundesplatz
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Frauenbewegung politischer Rahmen;politisches Leben (allgemein);politisches Leben (speziell);Demonstration